2017
DOI: 10.1074/jbc.m117.779447
|View full text |Cite|
|
Sign up to set email alerts
|

AMP-activated protein kinase α1 promotes atherogenesis by increasing monocyte-to-macrophage differentiation

Abstract: Monocyte-to-macrophage differentiation, which can be initiated by physiological or atherogenic factors, is a pivotal process in atherogenesis, a disorder in which monocytes adhere to endothelial cells and subsequently migrate into the subendothelial spaces, where they differentiate into macrophages and macrophage-derived foam cells and cause atherosclerotic lesions. However, the monocyte-differentiation signaling pathways that are activated by atherogenic factors are poorly defined. Here we report that the AMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
65
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 55 publications
11
65
0
1
Order By: Relevance
“…Our observation of induction of autophagy in H1299 stable cells for PKM1 and PKM2 knockdown is consistent with a recent study by Zhang et al (35), wherein it was shown that AMPK regulated the expression of key autophagic marker ULK1 and LC3B in a FoxO3 (transcription factor)-dependent manner. It is well-known that AMPK directly stimulates autophagy by phosphorylating Ulk1 at Ser-317 and Ser-777 residues (36).…”
Section: Discussionsupporting
confidence: 93%
“…Our observation of induction of autophagy in H1299 stable cells for PKM1 and PKM2 knockdown is consistent with a recent study by Zhang et al (35), wherein it was shown that AMPK regulated the expression of key autophagic marker ULK1 and LC3B in a FoxO3 (transcription factor)-dependent manner. It is well-known that AMPK directly stimulates autophagy by phosphorylating Ulk1 at Ser-317 and Ser-777 residues (36).…”
Section: Discussionsupporting
confidence: 93%
“…AMPK suppression of macrophage inflammation within plaques 228,230,251 and adipose tissue 219 may also be important for suppressing atherosclerosis development. In addition to regulating macrophage polarization, increased proliferation of monocytes to macrophages and reductions in autophagy are important for atherosclerosis 252 , and in this regard, AMPK inhibition of cellular proliferative pathways such as mTOR and p53 as well as the induction of autophagy would be expected to reduce atherosclerosis progression 253 ; however, this has not been observed in all studies 254 . Similarly, the induction of autophagy may reduce atherosclerosis and improve plaque stability, further supporting the possible beneficial role of activating macrophage AMPK 255 .…”
Section: ) (Table 1)mentioning
confidence: 99%
“…FOXO3 is an indirect GR target through the activation of SGK1 that alleviates the inhibition of Foxo3 transcriptional activity, which is synergized with the activation of FOXO3 transcriptional activity by AMPK. FOXO3 was shown to be required for the differentiation of monocytes into macrophages via activation of AMPKa1 and autophagy (Zhang et al, 2017b) and to promote anti-viral response in macrophages (Zhang et al, 2019b). Strikingly, FOXO3 is involved in the GC-driven anti-inflammatory response in Systemic Lupus Erythematosus through the reinforcement of the blockage of NF-KB activity (Lu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%